2020
DOI: 10.21608/jfds.2020.106390
|View full text |Cite
|
Sign up to set email alerts
|

Production of Nutraceutical Probiotic Whey–Based Beverage Fortified with Annona squamosal L (Custard Apple ) Fruit إنتاج مشروب شرش حیوى مغذى مدعم بفاکهة (ثمرة القشدة) Annona squamosal L

Abstract: Probiotic whey-based custard apple beverages (P.C.A.B.) were prepared with different combinations of whey and custard apple pulp juice , PJ (75:25, 50:50 and 25:75 , weight :weight) and inoculated with1% probiotic bacteria Lactobacillus casei. Beverages were evaluated for physic-chemical, microbiological and sensory properties, during cold storage. Total solids and the apparent viscosity were increased in (P.C.A.B.) treatments as the level of P.J. increased, whereas values of titratable acidity (T.A) were decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Whey‐based beverages (WBBs) can be made using either sweet CW or milk enriched with WPC or WPI (Seyhan et al., 2015). Furthermore, WPCs have a unique solubility that makes them suitable for use in a variety of beverages, such as fruit juices, soft drinks, wine, and aperitifs (2020 Guimarães et al., 2019; El‐Aidie, Hatem, et al., 2020). WBBs are considered refreshing, light, and a genuine thirst quencher (Panghal et al., 2018).…”
Section: Advantages and Applications Of Whey Proteins In Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Whey‐based beverages (WBBs) can be made using either sweet CW or milk enriched with WPC or WPI (Seyhan et al., 2015). Furthermore, WPCs have a unique solubility that makes them suitable for use in a variety of beverages, such as fruit juices, soft drinks, wine, and aperitifs (2020 Guimarães et al., 2019; El‐Aidie, Hatem, et al., 2020). WBBs are considered refreshing, light, and a genuine thirst quencher (Panghal et al., 2018).…”
Section: Advantages and Applications Of Whey Proteins In Food Industrymentioning
confidence: 99%
“…For example, a study by Dhadge et al (2019) found that incorporating 5% WPC solids into cow milk for khoa production improved its sensory characteristics. Several studies found that WPs, such as WPC, WPI, and whey permeate, are rich in bioactive compounds that can improve the texture, flavor, and overall quality of fermented milk beverages while also increasing their nutritional value, shelf life, and reducing waste (Janiaski et al, 2016;El-Aidie, Hatem, et al, 2020;Sohrabi et al, 2016). The application of fresh AW represents an accessible and sustainable approach to producing functional probiotic products that can benefit small dairy factories (Elgarhi et al, 2020;Skryplonek & Jasińska, 2015).…”
Section: Beverages and Fermented Drinksmentioning
confidence: 99%